Contrasts in religion, community, and structure at three homeless shelters - Jindra, Ines W., author.
1 online resource.
Keywords: "How do people in poverty and homelessness change their lives and get back on their feet? Homeless shelters across the world play a huge role in this process. Many of them are religious, but there is a lot of diversity in faith-based non-profits that assist people affected by poverty and homelessness. In this timely book, the authors look at three homeless shelters that take more or less intensive approaches to faith, community, and programming. In one shelter, for instance, residents are required to do a program of classes that includes group Bible study, worship, and self-evaluation. The other two examined are significantly less faith-based, but in different ways and with different structures. The authors show how the three shelters tackle homelessness differently, drawing on narrative biographical interviews and case studies with residents, interviews with staff, and case study research of the three shelters. Entering into significant debates in social theory over religion, agency, cognitive action, and culture, this book is important reading for scholars and students in religious studies, sociology and social work"--